An analysis of the integration of sustainability concepts into blockchain technology - Eligüzel, Nazmiye (International Journal of Applied Methods in Electronics and Computers, 2023)
The acceleration of data production and consumption due to the transition to an information society and industrial revolutions has had a significant impact on the expansion of the global economy. The emergence of Industry 4.0 has led to the adoption of various technologies, including blockchain, which is known for its potential to transform different domains through its solutions. This is particularly relevant in the context of data governance. Thus, blockchain technology has the potential to enhance the sustainability of diverse industries. Sustainability is a crucial concept that refers to the capacity to meet the requirements of the current generation without compromising the ability of future generations to do so.  The integration of blockchain technology across diverse industries holds the potential to greatly improve sustainability efforts. The objective of this study is to assess the relationship between blockchain technology and sustainability through a descriptive review of literature utilizing the latent semantic analysis topic modeling and clustering method, which is a social spider optimization technique. This study focuses on analyzing the impact of blockchain technologies on the sustainability sector. A corpus of 1069 papers has been sourced from the Scopus database. The results underscore the significance of cybersecurity, supply chain management, and the circular economy in the extant academic literature. The broad recognition of the supply chain domain's importance is evident in its application of blockchain technology and adherence to the sustainability principle. The present research focuses on the analysis and assessment of topics pertaining to traceability, cyber security, circular economy, energy, and transparency.